Food (In)Security, Human (In)Security, Women's (In)Security: State Policies and Local Experiences in Rural Rwanda. Issue 4 (1st October 2016) - Nzayisenga, Marie Jeanne; Orjuela, Camilla; Schierenbeck, Isabell
ABSTACT: Despite the growing importance of the concept human security, security studies in Africa remain largely focused on the threat of direct violence and the role of state actors. This article broadens the security agenda by focusing on food security and discusses how women in rural Rwanda experience and view food security. In making individual women the referent of security, the article exposes the gap between national level reforms, which aim to and have been deemed successful to combat poverty and increase food production, and the experiences of women who report a decline in food availability and increased problems in accessing food in the wake of reforms and who often struggle against hunger in a disadvantaged position within their households and local power structures. Building on 51 interviews with women in western Rwanda conducted in 2013 and 2014, the article illustrates how the human security perspective with a sensitivity to gender relations and positions is important for gaining a fuller picture of the security of individuals.